Umsetzung des Konzepts einer modernen Ressortforschung im Geschäftsbereich des BMU. - Böcher, Michael; Krott, Max (My University, 2010)
Ziel des Forschungsvorhabens war es, Kriterien für eine gute Ressortforschung zu entwerfen, um zur Qualitätssicherung in den im Geschäftsbereich des BMU bestehenden Bundesoberbehörden (UBA, BfN und BfS) beizutragen. Dazu wird ein neues Modell der Ressortforschung als wissenschaftsbasierte Politikberatung entwickelt, das an die aktuelle Forschungspolitik, an den aktuellen Stand der Wissenschaftsforschung und an die Praxis der Ressortforschung anschlussfähig ist. Aus dem Modell werden Qualitätskriterien abgeleitet und erläutert. Abschließend wird aufgezeigt, wie diese Qualitätskriterien ausgewählte bestehende Qualitätssicherungsmaßnahmen verbessern können und welche ergänzenden Qualitätssicherungsmaßnahmen hilfreich sein können. Ein Überblick über die Qualitätskriterien in Tabellenform schließt den Bericht als Anhang ab.

The aim of the research project Implementation of the concept of modern departmental research within the portfolio of the BMU was to develop criteria for good departmental research as a contribution to the quality assurance of the three subordinate authorities of the German Federal Ministry for the Environment, Nature Conservation and Nuclear Safety (BMU): the German Federal Environment Agency (UBA), the Federal Agency for Nature Conservation (BfN), and the Federal Office for Radiation Protection (BfS). For this aim a new model of departmental research as science-based policy advice has been developed which ties up with current developments in (1) research policy, (2) science studies, and (3) the practice of departmental research. Based on the model quality criteria are derived and explained. Subsequently it is shown how these quality criteria may improve existing measures of quality assurance as well as which additional quality assurance measures can be helpful. Finally, an overview over the quality criteria is provided in three tables.
Keywords: Theorie; Politikwissenschaft; Ministerium; Behörde; Forschung; Ressortforschung; Politikberatung